2017
DOI: 10.1080/16089677.2017.1299975
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and kidney disease: hidden consequences of the epidemic

Abstract: Obesity has become a worldwide epidemic, and its prevalence has been projected to grow by 40% in the next decade. This increasing prevalence has implications for the risk of diabetes, cardiovascular disease and also for chronic kidney disease. A high body mass index is one of the strongest risk factors for new-onset chronic kidney disease. In individuals affected by obesity, a compensatory hyperfiltration occurs to meet the heightened metabolic demands of the increased bodyweight. The increase in intraglomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
1
7
0
3
Order By: Relevance
“…Numerous studies have demonstrated an association between obesity and chronic kidney disease (CKD) [1]. Higher body mass index (BMI) has been associated with lower estimated glomerular filtration rate (eGFR), loss of eGFR over time, and incident end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated an association between obesity and chronic kidney disease (CKD) [1]. Higher body mass index (BMI) has been associated with lower estimated glomerular filtration rate (eGFR), loss of eGFR over time, and incident end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the deleterious effects of obesity are mediated by comorbid conditions including hypertension and diabetes. Obesity may also impact the kidneys directly by its effects on adipokines, inflammation, oxidative stress, activation of the renin-angiotensin-aldosterone system, sympathetic activation, insulin resistance, and abnormal lipid metabolism [1].…”
Section: Introductionmentioning
confidence: 99%
“…This study found an increasing BMI and abnormal WHR as risk factors for developing KD amongst NSAIDs users. Kovesty et al [22] found that obesity associated hyperfiltration leads to increased intraglomerular pressure and kidney damage. Increasing mean SBP and DBP were found to be risk for developing KD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pressure inside the glomerulus can cause serious damage to the kidneys and increase the risk of chronic kidney disease in a long period. It can also be a risk factor for nephrolithiasis and several kidney malignancies, including kidney cancer [2]. The kidneys are involved in regulating the body's osmolarity, stabilizing the internal environment (i.e.…”
Section: Introductionmentioning
confidence: 99%